Optimal Operation of Distribution Networks through Clearing Local Day-ahead Energy Market - Bahramara, Salah; Sheikhahmadi, Pouria; Lotfi, Mohamed; Catalão, João P. S.; Santos, Sérgio F.; Shafie-khah, Miadreza (IEEE, 2019)
New energy market players such as micro-grid aggregators (MGA), distributed energy resource aggregators (DERA), and load aggregators (LAs) have all emerged to facilitate the integration of DERs into power systems. These players can participate in wholesale markets either individually or through distribution companies (Discos). In both cases, several operational challenges emerge for transmission system operators (TSOs) and distribution system operators (DSOs). Meanwhile, a transition is occurring from centralized wholesale markets into local energy markets (LEMs). A literature review shows that these LEMs are mostly modeled focusing on the coordination between DSOs and TSOs to meet demand in real-time operation using ancillary service markets and balancing markets. The main contribution of this paper is to model a local day-ahead energy market (LDEM) for optimal operation of a distribution network. This LDEM is cleared by the DSO with the aim of maximizing the social welfare of market players while satisfying the technical constraints of the network. To investigate the effectiveness of the proposed model, it is applied on the IEEE 33-bus network. Moreover, the effect of technical constraints of the network on the distribution locational marginal price (DLMP) is studied.
Keywords: Distributed resources; Locational marginal price; distribution system operator; Local energy market; fi=Sähkötekniikka|en=Electrical Engineering|